2021
DOI: 10.3390/molecules26164880
|View full text |Cite
|
Sign up to set email alerts
|

Oral Supplementation with Hydrolyzed Fish Cartilage Improves the Morphological and Structural Characteristics of the Skin: A Double-Blind, Placebo-Controlled Clinical Study

Abstract: Collagen and its peptides are natural ingredients used in food supplements and nutricosmetics with the claim of providing benefits for skin health and beauty. In this context, the aim of the present study was to evaluate the clinical efficacy of oral supplementation with hydrolyzed fish cartilage for the improvement of chronological and photoaging-induced skin changes. A total of 46 healthy females aged 45 to 59 years were enrolled and divided into two groups: G1—placebo and G2—oral treatment with hydrolyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
0
9
0
4
Order By: Relevance
“…Regarding the absorption of FCH, the literature lacks relevant kinetics data; thus, this study also aimed at evidencing and characterizing the bioavailability of FCH in humans in order to both reinforce the clinical value of our previous results on skin health in middle-aged women [ 29 ] and to move forward on the mechanism of action at the cellular level.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding the absorption of FCH, the literature lacks relevant kinetics data; thus, this study also aimed at evidencing and characterizing the bioavailability of FCH in humans in order to both reinforce the clinical value of our previous results on skin health in middle-aged women [ 29 ] and to move forward on the mechanism of action at the cellular level.…”
Section: Discussionmentioning
confidence: 95%
“…It was recently shown that the supplementation of middle-aged healthy women with this FCH led to both a significant reduction in wrinkles and an increase in dermis density [ 29 ]. In this clinical ex vivo approach, considering the physiological processes of nutrients along the digestive track, we demonstrated that this FCH was absorbed and that the circulating metabolites produced in humans following FCH intake stimulate human dermal fibroblast growth, promote specific hyaluronan production, up-regulate elastin synthesis and inhibit MMP-1 and 3 expressions along with the enhancement of TGF-β release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, the alcalase-hydrolyzed cartilage of shark ( P. glauca ) exerts anti-hyperuricemic activity after oral administration to rats ( Murota et al, 2014 ). In addition, a double-blind, placebo-controlled clinical study reported oral supplementation with hydrolyzed fish cartilage improves the morphological and structural characteristics of the skin ( Maia Campos et al, 2021 ). These results suggest that fish cartilage hydrolysates or peptides have potential as functional foods or in other fields.…”
Section: Potential Bioactive Compounds In Fish Cartilagementioning
confidence: 99%
“…In the clinical evaluation, the participants also experienced a reduction in wrinkles, improvement in skin texture, firmness and appearance as well as a moisturising effect. Skin relief was evaluated using the Visioscan, 20 MHz ultrasound, microscope and high-resolution digital camera [10]. A randomised, placebo-controlled, double-blind trial was conducted in 99 healthy Japanese women receiving 1 or 5 g of collagen peptides or placebo once daily for 12 weeks.…”
Section: Effects Of Oral Hydrolysed Collagen Supplementation In Rando...mentioning
confidence: 99%